Impact Analysis of Digitalization, Technology Skills, and Social Inclusion on Social and Economic Change in Indonesia - Loso Judijanto; I Wayan Jata; Mislan Sihite; Bambang Purwoko; Risman Saripudin (West Science Social and Humanities Studies, 2024)
This research investigates the intricate interplay between digitalization, technology skills, social inclusion, and their collective impact on social and economic change in Indonesia. The study employs Structural Equation Modeling with Partial Least Squares (SEM-PLS) on a diverse sample of 150 participants, spanning various demographics and geographic locations. The results reveal significant positive relationships between digitalization, technology skills, social inclusion, and social and economic change. Digitalization emerges as a driving force for economic transformation, while technology skills and social inclusion play pivotal roles in shaping employment opportunities and contributing to societal advancement. The findings hold critical implications for policymakers, educators, and businesses aiming to foster a digitally inclusive and economically progressive landscape in Indonesia.